การแตกตัวของน้ำมันดินเบาช่วยโดยพลาสมาในเตาปฏิกรณ์ ไกลดิงอาร์ค - อัครศานต์ กรรณิกา (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Producer gas derived from biomass can be used as a renewable energy source in place of fossil fuels.In generating producer gas, there is also unwantedsubstance(tar)that should be got rid of. One method to remove taris by plasma. In this work, naphthalene was used as a model light tar. Pulsed power DC supply was employed to generate plasma in gliding arc configuration. Maximum outputvoltage of 20 kV at the frequency andduty cycleof20 kHzand 25% was used.Inthis experimenttheconcentration ofnaphthaleneinaccordance with theamounts found intypical biomass gasifier.It willdifferentiate theconcentration as average low concentration was 210.80 mg/m3 at nitrogen flow 5 l/min and 50 ℃ of water bath, average medium concentration was 479.42 mg/m3 at nitrogen flow 15 l/min and 50 ℃ of water bath, averagehigh concentration was 803.81 mg/m3 at nitrogen flow 10 l/min and 70 ℃ of water bath. Destruction efficiency at 15 % duty cycle of single stage reactor be valuable in the rage of 13.36 – 25.01% with energy density of 5085.97 – 6152.69 kJ/m3 at supplied power of 106 – 247 W. And destruction efficiency at 25 % duty cycle of single stage reactor be valuable in the rage of 64.04 – 87.12% with energy density of 4710.74 – 6502.19 kJ/m3 at supplied power of 342 – 947 W. For destruction efficiency at 25 % duty cycle of two stage reactor be valuable in the rage of 89.44 – 100% with energy density of 5784.00 – 6654.74 kJ/m3 at supplied power of 482 – 1374 W. The destruction efficiency was depend on % of duty cycle. When adding % of duty cycle willincrease watt was increase too. It is expected that high efficiency can be achieved at low energy input.